2016
DOI: 10.1186/s12885-016-2414-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival and BRCA status in male breast cancer: a retrospective single-center analysis

Abstract: BackgroundMale breast cancer (MBC) is rare. Given the paucity of randomized trials, treatment is generally extrapolated from female breast cancer guidelines.MethodsThis is a retrospective analysis of all male patients presenting with MBC at the Department of Oncology at University Federico II of Naples between January 1989 and January 2014. We recorded the following data: baseline characteristics (age, height, weight, body mass index, risk factors, family history), tumor characteristics (side affected, stage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 45 publications
5
31
1
Order By: Relevance
“…4 ) with TWIST1 methylation (HR:4.7, 95% CI:2.0–27.5, p = 0.01) also being associated with a significantly shorter survival in the BRCA2 MBC subgroup. Because BRCA2 tumours have higher methylation overall and also worse survival than other MBC cohorts [ 45 , 46 ], we also evaluated survival within the BRCA2 carriers, and observed a trend towards worse outcome with higher AMI in this sub-group (HR:3.3, 95% CI: 0.8–9.7, p = 0.1). Hypermethylation of FOXC1 (HR:2.3, 95% CI:0.99–8.1, p = 0.053) showed a strong trend towards worse DSS; hypermethylation of other genes showed no prognostic information.…”
Section: Resultsmentioning
confidence: 99%
“…4 ) with TWIST1 methylation (HR:4.7, 95% CI:2.0–27.5, p = 0.01) also being associated with a significantly shorter survival in the BRCA2 MBC subgroup. Because BRCA2 tumours have higher methylation overall and also worse survival than other MBC cohorts [ 45 , 46 ], we also evaluated survival within the BRCA2 carriers, and observed a trend towards worse outcome with higher AMI in this sub-group (HR:3.3, 95% CI: 0.8–9.7, p = 0.1). Hypermethylation of FOXC1 (HR:2.3, 95% CI:0.99–8.1, p = 0.053) showed a strong trend towards worse DSS; hypermethylation of other genes showed no prognostic information.…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 ] For male breast cancer, the main treatment mode is axillary lymph node dissection for clinically node-positive patients or sentinel lymph node surgery based on sentinel lymph node pathology. [ 5 , 6 ] These invasive operations often have a considerable impact on the quality of life of patients, which damaged their psychosocial function even after breast reconstruction surgery. [ 7 ] As a result, some patients may refuse the recommended surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 14% of men diagnosed with breast cancer are found to harbor a BRCA 2 mutation [ 8 ]. Two prior studies have reported worse prognosis in male breast cancer patients with a deleterious BRCA 1/2 mutation compared to those without a mutation [ 9 , 10 ]. However, both studies were limited by their small sample size.…”
Section: Introductionmentioning
confidence: 99%